Working class youth transitions as a litmus test for change: labour crisis and social conflict in Arab Mediterranean countries. Issue 3 (27th May 2021) - Paciello, Maria Cristina; Pioppi, Daniela
ABSTRACT: The article reconceptualizes the issue of youth precariousness and unemployment by taking empirical data from five Arab Mediterranean countries, namely Morocco, Tunisia, Egypt, Occupied Palestinian Territories and Lebanon. It demonstrates that youth worsening labour conditions point not only to the problems of a specific age-cohort in entering the labour market but also to a much larger process of change that can be best understood as the creation of a new working class which is by far more precarious and fragmented than the post-independence one. The reaction to the profound reconfiguration of labour relations is intense, as the unparalleled labour-related protests in the region demonstrate. However, current dynamics of mobilization reveal many tensions between wage, secure workers, and precarious unemployed youth, as well as between secure-workers themselves due to growing fragmentation of the working class, but also to repressive and divide et impera strategies carried out by regimes.